Numerical modeling of evolving discontinuities in rocks using solid interface finite elements - Maedo, M. A. (2019)
This work presents a numerical technique capable of handling evolving fractures in rocks that allows extending, in a simple manner, standard finite element programs developed for geological (continuum) media to deal with the presence of discontinuities. The proposed mesh fragmentation technique consists in introducing especial (high-aspect ratio finite elements) in-between the regular (bulk) finite elements. This methodology has been successfully used to model both, drying cracks in soils and fractures in concrete structures. The proposed approach is fully coupled and has been implemented in the finite element program CODE_BRIGHT, which was especially developed to tackle coupled thermo-hydro-mechanical problems in geological media. The paper presents the main components of the proposed approach and its implementations in CODE_BRIGHT. It also discusses the main advantages and shortcomings associated with this technique. The proposed method is verified and validated using available analytical and numerical solutions associated with the problem of hydraulic fracturing in rocks. The technique is also applied to solve engineering problems involving the formation and propagation of discontinuities in geo-materials. A very satisfactory performance of the proposed method is observed in all the analyzed cases.